NONTUBERCULOUS MYCOBACTERIAL DISEASE IN A GENERAL HOSPITAL - AKITA, Yuko; YAMADA, Yuka; NISHIO, Masayuki; SATO, Shigeki; MASE, Yuji; NIIMI, Takashi; YAMAMOTO, Masahiko; MAENO, Ken; YOSHIKAWA, Kosho (Kekkaku, 1999)
Annual incidence of nontuberculous mycobacterial (NTM) disease has been gradually increasing in the last 10 years in Japan. It is likely to encounter this disease not only in hospitals specialized in mycobacterial diseases but also in general hospitals. NTM were isolated from 97 cases between January 1990 and June 1996 at our hospital. Out of them, 41 patients were diagnosed as NTM disease. Mycobacterium avium complex (MAC) was the most frequent pathogens (68.3%) and M. kansasii (22%) was the next. Other pathogens were M. chelonae (4.9%), M. fortuitum (2.4%) and M. szulgai (2.4%). Results obtained in our hospital were very similar to the rates which have been reported previously. Patients with MAC infection showed relatively poor prognosis (eight patients were died out of 28 patients with MAC) in this study compared with the cases reported in previous papers, and this result could be explained by the severity of illness when they were admitted to our hospital, the insufficiency of the initial treatment which should be stared with the combined use of three to four antibacterial drugs including clarithromycin, and to a low dosage of clarithromycin compared with conventionally adopted dosage. Unlike tuberculosis, human to human transmission is considered to be negligible in the case of NTM disease, and general hospitals are able to provide medical care to the patients with NTM disease. Rather, if general hospitals which are located in the region near to the patients residence can play more active role in the treatment of NTM disease, it would be more beneficial to patients requiring long-term follow-up observation. Based on the result that similar therapeutic results were obtained for infections with other NTM as reported in previous papers, it is indicated that general hospitals are able to provide medical care to patients with NTM disease if therapeutic regimens recommended by specialist are sufficiently understood and applied.